Cognitive Impairment Following Acute Mild Traumatic Brain Injury - de Freitas Cardoso, Maíra Glória; Faleiro, Rodrigo Moreira; de Paula, Jonas Jardim; Kummer, Arthur; Caramelli, Paulo; Teixeira, Antônio Lúcio; de Souza, Leonardo Cruz; Miranda, Aline Silva (Frontiers in Neurology, 2019)
Patients with mild traumatic brain injury (mTBI) may present cognitive deficits within the first 24 h after trauma, herein called “acute phase,” which in turn may lead to long-term functional impairment and decrease in quality of life. Few studies investigated cognition in mTBI patients during the acute phase. The objectives of this study were to investigate the cognitive profile of patients with mTBI during the acute phase, compared to controls and normative data, and whether loss of consciousness (LOC), previous TBI and level of education influence cognition at this stage. Fifty-three patients with mTBI (aged 19–64 years) and 28 healthy controls participated in the study. All patients were evaluated at bedside within 24 h post-injury. Demographic and clinical data were registered. Cognitive function was assessed with the Mini-mental state examination (MMSE), the Frontal Assessment Battery (FAB), Digit Span (working memory), and the Visual Memory Test/Brief Cognitive Battery (for episodic memory). The clinical sample was composed mainly by men (58.5%). The mean age was 39 years-old and 64.3% of the patients had more than 8 years of education. The most common causes of mTBI were fall from own height (28.3%), aggression (24.5%), and fall from variable heights (24.5%). Compared to controls, mTBI patients exhibited significantly worse performance on MMSE, FAB, naming, incidental memory, immediate memory, learning, and delayed recall. Compared to normative data, 26.4% of patients had reduced global cognition as measured by the MMSE. Episodic memory impairment (13.2%) was more frequent than executive dysfunction (9.4%). No significant differences were found in cognitive performance when comparing patients with or without LOC or those with or without history of previous TBI. Patients with lower educational level had higher rates of cognitive impairment (VMT naming−28.6 vs. 4.2%; VMT immediate memory−32 vs. 4.2%; VMT learning−39.3 vs. 4.2%, all p < 0.05). In sum, we found significant cognitive impairment in the acute phase of mTBI, which was not associated with LOC or history of TBI, but appeared more frequently in patients with lower educational level.